Contemporary Results and Clinical Utility of Renal Mass Biopsies in the Setting of Ablative Therapy: A single center experience. (2020) - Ma, Lucy X; Craig, Kiersten M; Mosquera, Juan Miguel; Robinson, Brian D; Scherr, Douglas S; Pizzo, Joseph Del; McClure, Timothy D; Khani, Francesca
Highlights: We evaluated the clinical utility of renal mass biopsy in the setting of ablative therapy in a single institutional cohort enriched for small renal masses Small mass size, cystic lesions, and fewer number of passes were significantly associated with a non-diagnostic result. We recommend a separate biopsy procedure prior to ablation when a renal mass is particularly small or cystic. Our study also highlights a higher incidence of clear cell papillary renal cell carcinoma among renal masses than has been historically described, likely owing to its prevalence amongst small renal masses. Abstract: Purpose: Clinical guidelines have recently included renal mass biopsy (RMB) in management algorithms, especially in the setting of small renal masses ≤ 4 cm (SRM) and ablative therapy. We sought to evaluate the diagnostic rates of RMB, factors associated with a non-diagnostic biopsy, its clinical utility, and its safety profile in the setting of ablative therapy. Materials and Methods: A total of 174 RMB from 167 patients, performed in a tertiary academic center from 01/2015 to 01/2019, were included. Patient demographics, radiographic mass size, RMB diagnoses, subsequent clinical management, and complications were retrospectively reviewed. RMBs were classified as diagnostic or non-diagnostic based on set criteria. Results: The mean mass size was 3.0 cm (range: 0.5-15.3 cm) and 140 biopsies (80%) were SRM. Among all RMB, 159 (91%) were diagnostic and 15 (9%) were non-diagnostic. Non-diagnostic biopsies were associated with small mass size, the presence of a cystic component (p < 0.00001) and fewer number of cores submitted (p = 0.0046). All non-diagnostic biopsies occurred in SRMs, where the mean mass size was significantly smaller than diagnostic biopsies (1.3 versus 3.2 cm, p = 0.001). RMB with concurrent ablation yielded non-diagnostic results more frequently than isolated RMBs (15% vs 2%, respectively). Conclusions: RMB is useful for definitive diagnosis and clinical management in the setting of ablative therapy. Small mass size, cystic lesions, and fewer number of passes obtained are associated with non-diagnostic biopsies. When a renal mass diagnosis is particularly critical, a separate biopsy procedure prior to ablative therapy is recommended.